Traditional taxis vs automated taxis – Does the driver matter for Millennials?. (October 2020) - Pakusch, Christina; Meurer, Johanna; Tolmie, Peter; Stevens, Gunnar
Highlights: The impact of automated taxis on traditional taxis are analyzed empirically. Millennials' taxi rides are particularly suitable to be performed by automated taxis. Interaction with the human driver does not justify the use of a traditional taxi. Taxi cost rather than the fate of taxi drivers determine the Millennials' decision. The Advent of Automated Taxis Poses a Threat to Public Transportation. Abstract: It is anticipated that autonomous vehicles will have a huge impact on the creation of sustainable smart cities and communities. One of the key concerns regarding autonomous vehicles is how automation may threaten jobs in the transport industry, including the traditional role of taxi drivers. To begin to explore how important an actual taxi driver is to customers and the extent to which they might be happy to have autonomous taxis replace traditional taxis, we conducted qualitative interviews with 34 Millennial-aged participants. These were problem-centered narrative interviews, largely conducted face-to-face, and analyzed using thematic analysis. Millennials were focused upon because, given current figures and likely future projections of use, they form the key market for prospective future autonomous taxis. The results show that the kind of taxi rides Millennials make are particularly suitable for automated taxis because interaction with a human driver is not a high priority for this group, while the prospect of autonomous taxis being cheaper is . Meanwhile the fate of taxi drivers does not play a significant part in how Millennials reason about this. An incidental finding, here, is that, by offering a convenient and affordable alternative, the advent of automated taxis may also pose a threat to public transportation.